2017
DOI: 10.1007/s00423-017-1552-2
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of surgery in patients with non-variceal upper gastrointestinal bleeding

Abstract: UGIB remains challenging and endoscopy is the first choice of intervention. Care must be taken once a patient is taking antirheumatic non-steroidal pain medication and suffers from cancer. In patients with presence of liver cirrhosis, an earlier surgical intervention may be considered, in particular for patients with recurrent bleeding. Embolization is not widely available and carries the risk of necrosis of the affected organ and should be restricted to a subgroup of patients not primarily eligible for surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…Our data shows that the role of emergency surgery still continues to diminish in Finland. This result is different from recently published German investigation, where it was found that 17% of patients with UGIB needed emergency surgery with overall mortality of 22% [16]. The high rate of morbidity and mortality associated with surgical treatment for UGIB has been recently published elsewhere as well [8].…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Our data shows that the role of emergency surgery still continues to diminish in Finland. This result is different from recently published German investigation, where it was found that 17% of patients with UGIB needed emergency surgery with overall mortality of 22% [16]. The high rate of morbidity and mortality associated with surgical treatment for UGIB has been recently published elsewhere as well [8].…”
Section: Discussioncontrasting
confidence: 55%
“…Over the past decade, mortality has not decreased in the elderly patients requiring surgery for acute UGIB [15, 16]. Recent German audit reported that 17% of UGIB patients needed emergency surgery with an overall mortality rate of 22% [16]. The purpose of our retrospective audit was to evaluate the incidence of UGIB in the elderly patients, cardiovascular risk factors for bleeding, therapeutic options, and especially the need for urgent surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although patients with GBS = 0 are considered safe for discharge, care must be taken with patients with some comorbidities and history of peptic ulcer since these factors have been shown to act as an independent risk factor for mortality and endoscopic intervention [3,8]. Since hypoalbuminemia is associated with several comorbidities, we assume using a combined model of Albumin-GBS may help clinician in their judgement for safer discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, recent studies have found some risk factors independently predicting adverse outcomes. These risk factors include: history of peptic ulcer [3], increase in BUN [4], hemodynamic instability, lower serum sodium, hemoglobin and platelet count [5,6], combination of tumor and NSAIDs, liver cirrhosis and coagulopathy [7,8], higher serum bilirubin, creatinine [9], lactate [10,11] and lower serum albumin [12].…”
Section: Introductionmentioning
confidence: 99%